The importance of integration of education for sustainable development in tertiary education - an example of good practice in teaching ESP - Rubić, Ivana (Crisis Management Days, 2024)
Tertiary education is a system that enables students to acquire knowledge and skills in certain disciplines, but also for their overall development, because it is necessary to develop the critical thinking and problem-solving skills in students necessary to solve complex issues of sustainability in their future careers and society. The integration of Education for Sustainable Development (ESD) into the curriculum of various courses transcends traditional academic boundaries and is an example of a holistic approach to education. In today's changing world, there is a great need for experts who can contribute to sustainable solutions. Tertiary education institutions have a responsibility to prepare students to understand and address sustainability issues by including ESD in the curricula of various courses so that students become environmentally aware and socially responsible change makers who can promote sustainable development in their fields. In the field of pedagogy, ESD emphasizes a student-oriented approach to learning and, in this context, the use of innovative learning methods that actively engage students in the learning process and promotes education for responsible citizenship. Various forms of active research and project-based learning and forms of collaborative learning encourage critical thinking, problem solving and value-based decision-making as well as lifelong learning. The paper will present the ways of implementing innovative learning methods to promote ESD which are commonly used in foreign language teaching and which educators can use to create interesting, relevant and meaningful learning experiences that empower students to become informed, responsible and active agents of change for a sustainable future. Teaching ESP (English for specific purposes) provides a unique and valuable platform for implementing education for sustainable development. The paper will present examples of good practices of combining teaching ESP with sustainability topics and student-centered practices, for the purpose of developing language competences and understanding of sustainability issues.